The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/0394632015572557
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of MMP12 inhibits the growth and invasion of lung adenocarcinoma cells

Abstract: Matrix metalloproteinase-12 (MMP12) is involved in many pathological processes including cancer. The expression and function of MMP12 in lung adenocarcinoma (LAC) remain unclear. The present study aimed to investigate the correlation of MMP12 expression with LAC patients and clarify its role in growth and invasion of LAC cells. The expression of MMP12 in human LAC was examined by immunohistochemical assay using a tissue microarray procedure. A loss-offunction experiment was used for observing the effects of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 26 publications
5
35
1
Order By: Relevance
“…Matrix metalloproteinase-12 is involved in many pathological processes including cancer and it plays an essential role in invasion and metastasis of tumour cells. [17][18][19] Increased expression of MMP12 was observed in certain types of cancer, such as gastric cancer, 17 lung adenocarcinoma, 18 nasopharyngeal carcinoma 19 and cutaneous melanoma. 20 Knockdown of MMP12 inhibited proliferation and invasion of lung adenocarcinoma as well as nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinase-12 is involved in many pathological processes including cancer and it plays an essential role in invasion and metastasis of tumour cells. [17][18][19] Increased expression of MMP12 was observed in certain types of cancer, such as gastric cancer, 17 lung adenocarcinoma, 18 nasopharyngeal carcinoma 19 and cutaneous melanoma. 20 Knockdown of MMP12 inhibited proliferation and invasion of lung adenocarcinoma as well as nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…NSCLC patients with positive expression of MMP12 had a higher Hazard Ratio value for DFS and OS (1.72 (95%CI,1.30–2.26);1.73(95%CI1.28–2.54)). Knockdown of MMP12 inhibited proliferation and invasion of lung adenocarcinoma cells followed by the down-regulation of proliferating cell nuclear antigen (PCNA) and vascular endothelial growth factor (VEGF) [ 25 ].These results demonstrated that MMP12 played an important role in tumor invasiveness and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, MMP2 and MMP12 belong to the group of MMPs, which are known for their key role in tumor metastasis and invasiveness (30,31). Recent studies have shown that inhibition of MMP2 and MMP12 suppresses the invasion of gastric and lung cancers (32,33). …”
Section: Discussionmentioning
confidence: 99%